To evaluate the effect of COVID-19 pandemic and national lockdown on patient care at a tertiary-care ophthalmology institute - Babu, Naresh (Indian J Ophthalmol, 2020)
PURPOSE: To evaluate the effect of COVID-19 pandemic and national lockdown on patient care at a tertiary-care ophthalmology institute. METHODS: Records of all the patients who presented from March 25(th) to May 3(rd), 2020 were scanned to evaluate the details regarding the presenting complaints, diagnosis, advised treatment and surgical interventions. RESULTS: The number of outpatient department visits, retinal laser procedures, intravitreal injections and cataract surgeries during this lockdown decreased by 96.5%, 96.5%, 98.7% and 99.7% respectively compared from the corresponding time last year. Around 38.8% patients could be triaged as non-emergency cases based on history alone while 59.5% patients could be triaged as non-emergency cases after examination. Only eighty-four patients opted for video-consultation from April 15(th) to May 3(rd), 2020. Nine patients presented with perforated corneal ulcer, but could not undergo penetrating keratoplasty due to the lack to available donor corneal tissue. One of these patients had to undergo evisceration due to disease progression. Two patients with open globe injury presented late after trauma and had to undergo enucleation. Around 9% patients could not undergo the advised urgent procedure due to logistical issues related to the lockdown. CONCLUSION: A significant number of patients could not get adequate treatment during the lockdown period. Hospitals need to build capacity to cater to the expected patient surge post-COVID-19-era, especially those requiring immediate in-person attention. A large number of patients can be classified as non-emergency cases. These patients need to be encouraged to follow-up via video-consultation to carve adequate in-person time for the high-risk patients.